Replication of an origin-containing derivative of plasmid RK2 dependent on a plasmid function provided in trans - Figurski, David H. (1979)
pRK212.2, a derivative of the broad host range plasmid RK2, contains two EcoRI cleavage fragments, A and B, neither of which can replicate by itself in Escherichia coli. Fragment A (41.7 kilobases), but not fragment B (14.4 kilobases), can be cloned by insertion into the unrelated plasmids mini-F and ColE1. Fragment B contains the origin of replication and the ampicillin-resistance determinant of RK2. Transformation of E. coli cells containing the mini-F-fragment A hybrid plasmid with fragment B DNA results in the recircularization and replication of fragment B as a nonmobilizable plasmid (pRK2067) with the copy number and incompatibility properties of RK2. Fragment B cannot be cloned in the absence of fragment A because the latter fragment suppresses a function, specified by fragment B, that results in loss of host cell viability. A small segment (2.4 kilobases) of fragment B that contains the RK2 origin of replication but no longer affects host cell growth in the absence of fragment A had been cloned previously by insertion into a ColE1 plasmid. This hybrid plasmid, designated pRK256, will replicate in E. coli polA mutants only when a fragment A-bearing helper plasmid is present. These results demonstrate that the potentially lethal function specified by fragment B of RK2 is not necessary for replication and that at least one trans-acting function is directly involved in RK2 replication.